CONCEPT OF REASONING, LOGIC, SOURCES OF KNOWLEDGE, AND TRUTH CRITERIA OF MODERN SCIENCE - Khambali Khambali; Nanat Fatah Natsir; Erni Haryanti (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
The purpose of writing this work is to reveal an analysis of a number of concepts about the foundations of philosophy in terms of reasoning, logic, sources of knowledge and criteria for the truth of modern science in the tradition of Greek philosophical studies. This scientific activity uses literature studies by carrying out a series of library data collection activities, reading and taking notes, and managing study materials that are directed to answer research problems. The results of the study in this work resulted in the conclusion that knowledge will be obtained through a thought process by reasoning that can produce the latest knowledge. Knowledge can be acquired with or without the scientific method. However, not every knowledge is stated in accordance with the principle of truth based on logical procedures (rational and correct), be it naturalist logic (natural logic), or artificial logic (scientific logic). Every truth at the time of proving must be on the ontological status of the object, the epistemological attitude (with the way and attitude of how knowledge occurs), and finally with what axiological attitude.